Method development and validation of stability indicating UV method for simultaneous estimation of Lamivudine & Zidovudine in tablet dosage form - PRABHAT DESSAI,; NIRUPA FATREKAR, (International Journal of Pharma and Bio Sciences, 2018)
Lamivudine and Zidovudine combination is used to treat HIV/ AIDS. It is antiretroviral tablet. It is used together with other antiretrovirals. The present work describes a new simple, sensitive and precise UV Spectrophotometric method for the simultaneous estimation of Lamivudine and Zidovudine in bulk and in Pharmaceutical dosage forms. The Stability indicating method was developed and validated in the present work. The parameters Linearity, Precision, Accuracy, Robustness, LOD, LOQ, system suitability was studied as per the ICH guidelines. Lamivudine and Zidovudine shows maximum wavelength at 272 & 287 nm. The method was found to be specific without any interference and precise with %RSD less than 2. The LOD & LOQ were found to be 0.005 µg/ml and 0.013 µg/ml for Lamivudine & 0.014 µg/ml and 0.44 µg/ml for Zidovudine. The robustness results were satisfactory by changing the λmax by ±2nm. The accuracy of the method was determined by recovery studies obtained as 99.72%. The drugs showed degradation for acid, light and peroxide and no degradation for alkali while performing forced degradation studies. Thus the proposed method was found to be accurate, simple & can be used for routine analysis of combination of the drugs.